Functional neuroimaging in survivors of torture - Ramasar, Thriyabhavan (My University, 2012)
Survivors of torture may have long-term physical, psychiatric and psychological sequelae. The aim of this study was to determine whether survivors of torture exhibit any psychopathology, whether they demonstrate abnormal findings on Brain Single Photon Emission Computed Tomography (SPECT) imaging, and whether correlations exist between Post Traumatic Stress Disorder (PTSD), Major Depressive Disorder (MDD), perfusion changes on Brain SPECT and Initial Self Reporting Questionnaire (SRQ8) scores. Thirty-six volunteers were recruited in a non randomised manner. Participants were assessed by a psychiatrist. The SRQ8, Impact of Event Scale – Revised (IES-R) and Montgomery Asberg Depression Rating Scale (MADRS) were administered. Participants underwent Brain SPECT imaging to assess cerebral perfusion changes. Data was analysed using Statistica 9.1. The primary psychiatric diagnoses made were PTSD, MDD or both. Participants with psychopathology had higher SRQ8, MADRS and IES-R scores. Although qualitatively, participants with psychopathology showed increased abnormal cerebral perfusion on Brain SPECT imaging, as compared to those participants without psychopathology, this could not be proven statistically. Perfusion changes were noted in the temporal cortices, parietal cortices, orbitofrontal cortices, thalami and basal ganglia. Higher SRQ8 scores were associated with higher scores on the MADRS and IES-R, and hence correlated with diagnoses of MDD and PTSD, but no direct association was noted with the visualised abnormal Brain SPECT imaging findings.
Keywords: Diagnostic Imaging